2007
DOI: 10.1016/j.quaint.2006.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon chronology of the mammoth site at Niederweningen, Switzerland: Results from dating bones, teeth, wood, and peat

Abstract: The peat section at Niederweningen is a site of spectacular excavations of numerous bones of mammoth and other animals that was first recognized in the late 19th century. In 1987/1990, new excavations provided more peat material, which was radiocarbon dated to 33,000 14 C years BP and 42,000 14 C years BP. The first AMS radiocarbon ages of mammoth bones from 1890/1891 excavations placed the age between 33,000 14 C years BP and 35,000 14 C years BP. In this study, new results were obtained on bones, teeth, wood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 29 publications
(37 reference statements)
5
56
0
Order By: Relevance
“…This therefore implies that the human groups which visited Kraków Spadzista c.24ka 14 C yr BP experienced a colder climate than that tolerated by occupants of the Russian Plain, despite the fact that the Russian sites were located further north than Kraków Spadzista, and the differences in relative temperature between the sites today. The results are also 0.5-1.0‰ lower than those of mammoths at Niederweningen, the site of a mass death event from Switzerland firmly correlated to a GI event c.45-50ka cal BP by climatic and dating evidence (Tütken et al, 2007;Hajdas et al, 2007). This difference also likely reflects geographic and chronological differences in climate between the two sites.…”
Section: δ 18 O Data -Comparison With European-wide Resultsmentioning
confidence: 73%
“…This therefore implies that the human groups which visited Kraków Spadzista c.24ka 14 C yr BP experienced a colder climate than that tolerated by occupants of the Russian Plain, despite the fact that the Russian sites were located further north than Kraków Spadzista, and the differences in relative temperature between the sites today. The results are also 0.5-1.0‰ lower than those of mammoths at Niederweningen, the site of a mass death event from Switzerland firmly correlated to a GI event c.45-50ka cal BP by climatic and dating evidence (Tütken et al, 2007;Hajdas et al, 2007). This difference also likely reflects geographic and chronological differences in climate between the two sites.…”
Section: δ 18 O Data -Comparison With European-wide Resultsmentioning
confidence: 73%
“…), sometimes associated with complete Picea cones and even some fragmentary bones. The ages of a Picea cone (44,52071080 14 C yr BP) and a wood piece (42,6207780 14 C yr BP) (Hajdas et al, 2007) from this upper peat are similar to the age of the upper part of the mammoth peat. It is possible that this upper peat documents a short and slightly younger peat growth.…”
Section: Stratigraphy and Chronologymentioning
confidence: 60%
“…The radiocarbon ages of the upper mammoth peat at Niederweningen (Hajdas et al, 2007) suggest correlation to the warm period of the Dansgaard-Oeschger Event 12 in the Greenland ice core record.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…They showed that in spite of careful cleaning of the ultrafilter, small amounts of contaminant young carbon remained, which probably came from glycerin; hence, they recommended caution in the use of the ultrafilter. In at least one example, dates of mammoth bone samples have been obtained without ultrafiltration, where the ages compare well with contemporary peat and wood (Hajdas et al 2007). …”
Section: Introductionmentioning
confidence: 99%